The impact of governance structures on economic growth in Africa: a panel data analysis of 47 African countries - Appiah-Kubi, Seth Nana Kwame; Malec, Karel; Phiri, Joseph; Maitah, Mansoor; Kotaskova, Sylvie Kobzev; Mach, Jiri; Sirohi, Jitka (Technological and Economic Development of Economy, 2023)
Major international institutions like the World Bank, African Union, and International Monetary Fund have made the development of robust governance systems a “sacred utterance” since the 1990s. Our study aimed to refute this common thinking by examining how governance structures have affected the expansion of the financial market in 47 African countries from 2008 to 2019. Using the availability of venture capital as a proxy for financial market development, our article departed from existing literature which used stock exchange characteristics as benchmarks for growth in the financial market. The governance variables comprise the six global governance indices: control of corruption, government effectiveness, political stability, regulatory quality, the rule of law, and voice and accountability. The model’s control variables include GDP per capita, inflation, and trade openness. Our finding suggests that a great quality governance climate is significant in explaining the growth of the financial market in Africa using the generalized method of moments (GMM) methodological approach with corrected standard errors. Considering these findings, our research makes the case that solid institutional frameworks might encourage the degree of financial systems growth in Africa. Therefore, the financial development rate in the African region will be significantly influenced by improving the quality of governance through strengthening legal and institutional frameworks to facilitate financial inclusion.